Perceived nonwork constraints and withdrawal intention among expatriates during the COVID-19 pandemic: moderating role of resilience and marital status - Hak, Liong Chan; Zawawi, Dahlia; Yen, San Michelle Ng; Pei, Sung Toh (Behavioral Science Research Institute, Srinakharinwirot University, 2023)
The COVID-19 pandemic has posed a considerable threat to the wellbeing of expatriates, which can be seriously exacerbated by both work and nonwork-related factors. Since restrictions were introduced worldwide, expatriates find it more challenging to integrate into their organizations and local societies. This study mainly aimed to examine if resilience and marital status could affect the perceptions of nonwork constraints and withdrawal intentions among expatriates during the pandemic. Data collected from a sample of 205 expatriates living and working in Malaysia was analyzed using partial least squares structural equation modeling. The results showed the positive and direct effect of perceived nonwork constraints on withdrawal intention (β = .29, p = .30). Using the two-stage moderation analysis, the results indicated the significant moderating effect of marital status on the relationship between perceived nonwork constraints and withdrawal intention (β = -.14, p = .04). However, the results did not substantiate the moderating effect of resilience on the relationship between perceived nonwork constraints and withdrawal intention (β = .16, p = .07). This research contributes to behavioral science knowledge about global mobility by applying spillover theory and the conservation of resources theory in the context of a medical emergency like the COVID-19 crisis. Notwithstanding ongoing obstacles caused by the global pandemic, the research findings could provide implications for human resource practitioners to improve work behavior among expatriates by considering their nonwork aspects and marital status.